2009
DOI: 10.2471/blt.08.058065
|View full text |Cite
|
Sign up to set email alerts
|

Oesophageal corrosive injuries in children: a forgotten social and health challenge in developing countries

Abstract: Problem An unsafe environment is a risk factor for child injury and violence. Among those injuries that are caused by an unsafe environment, the accidental ingestion of corrosive substances is significant, especially in developing countries where it is generally underreported. Approach To address this challenging, unmet medical need, we started a humanitarian programme in Sierra Leone. By reviewing the current literature from developing countries and our own experience in the field, we developed a flowchart fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
73
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(85 citation statements)
references
References 11 publications
4
73
0
8
Order By: Relevance
“…Family organization classiied as extended implies crowded living conditions and enables both parents to work outside home while other family members take care of their children [18]. Other authors have reported that unsafe homes where safety rules regarding caustic substances are lacking have been identiied as a substantial risk factor for CI in children [1,9,13,17,21]. Sarioglu-Buke et al found that children from families where both parents with low educational level and low socioeconomic status had a higher risk for a CI event.…”
Section: Epidemiologymentioning
confidence: 99%
See 2 more Smart Citations
“…Family organization classiied as extended implies crowded living conditions and enables both parents to work outside home while other family members take care of their children [18]. Other authors have reported that unsafe homes where safety rules regarding caustic substances are lacking have been identiied as a substantial risk factor for CI in children [1,9,13,17,21]. Sarioglu-Buke et al found that children from families where both parents with low educational level and low socioeconomic status had a higher risk for a CI event.…”
Section: Epidemiologymentioning
confidence: 99%
“…In 1985, Wasserman reported that approximately 5000 children younger than 5 years ingested lye each year in the United States [2]; in 2008, the USA National Poison Data reported over 200,000 exposures to caustic substances [3]. Unfortunately, the true prevalence regarding this health problem is not known in most developing countries and cannot be extrapolated from publications of series of children with CI treated in paediatric hospitals; however, these publications describe demographic, clinical and treatment characteristics of children from low, lower-middle and high-income countries information is scarce specially in lower-middle income countries [1].…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…In these countries CI are more common than in westernized nations, in part because of the use of secondary containers and the availability of chemicals around the home. 15 In addition, with the westernization of developing nations and a rise in atopic diseases where food allergy was previously uncommon, the need to differentiate between CI and anaphylaxis in these settings is increasingly important. 16 …”
Section: Discussionmentioning
confidence: 99%
“…Accidental ingestion of corrosive substances is more commonly seen in early childhood with children younger than fi ve years being more prone to such ingestion 1,2,3,4,5,6 . Ingested corrosives are either acids or alkali 7 .…”
Section: Introductionmentioning
confidence: 99%